PENAYANGAN FILM TANPA IZIN OLEH TVRI BERDASARKAN UU NO. 28 TAHUN 2014 TENTANG HAK CIPTA - Faradila Sabrina; Aline Gratika Nugrahani (Reformasi Hukum Trisakti, 2022)
Copyright is an exclusive right that belongs to the inventor or right holder and is covered by legal protection. This implies that the author has the authority to let or forbid others from exploiting his creation. A film creator has issued a subpoena to TVRI, a government-owned broadcast organization, for his acts in airing the disputed movie without the creator's consent. A protected object under Article 40 of the 2014 Copyright Law No. 28 is film. The issue in this essay is whether TVRI, a government organization, needs permission to exhibit a copyrighted work and whether TVRI violates the law if it broadcasts a work without authorization. he nature of the research is descriptive and conclusions are drawn using the deductive method. Based on the results of TVRI's research, Article 5 paragraph (1) and Article 9 paragraph (1) of the Copyright Law and Article 7 paragraph (1) of the Public Information Disclosure Act were committed.